De-escalation towards omission is the tipping point of individualizing breast cancer surgery - Heil, Jörg; Pfob, André; Kuerer, Henry Mark (European journal of surgical oncology, 2020)
Tailoring of breast cancer treatment to the individual has especially occurred in breast cancer surgery: paradigms have changed from Halsted's radical mastectomy in 1882, to simple mastectomy, to lumpectomy. Within the next decade, we might face another paradigm change of omitting breast cancer surgery at all in case of a complete response after neoadjuvant systemic treatment. In this article, we provide an overview of the reasoning for this new paradigm change, the criticism it has evoked, and under which conditions it might be incorporated into clinical practice. We also take a look at previous paradigm changes in breast cancer surgery and the insights they provide us in the current situation on a statistical but also on a psychological level.